Periodontal pathogens and obesity in the context of cardiovascular risks across age groups - Leonov, Georgy; Varaeva, Yurgita; Livantsova, Elena; Vasilyev, Andrey; Vladimirskaya, Olga; Korotkova, Tatyana; Nikityuk, Dmitry; Starodubova, Antonina (Frontiers in Oral Health, 2025)
BackgroundCardiovascular diseases (CVDs) are the leading cause of mortality and morbidity among noncommunicable diseases. Over the past decade, there has been a notable increase in the prevalence of CVDs among young individuals. Obesity, a well-known risk factor for CVDs, is also associated with various comorbidities that may contribute to cardiovascular risk. The relationship between periodontal pathogens and CVD risk factors, including obesity, smoking, lipid metabolism disorders, and inflammatory markers, remains underexplored.MethodsThis study examined the relationship between six periodontal pathogens (Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Treponema denticola, Tannerella forsythia, Prevotella intermedia, and Fusobacterium nucleatum) and CVD risk factors among 189 subjects stratified by age and body mass index (BMI). Body composition was assessed via bioimpedance analysis, and blood samples were analyzed for lipid profiles, glucose, and proinflammatory cytokines. Oral samples were collected for polymerase chain reaction (PCR) analysis to identify periodontal pathogens. Cardiovascular and diabetes risk scores were calculated using the SCORE and FINDRISC scales.ResultsThe prevalence of periodontal pathogens in the population was 33.0% for P. gingivalis, 47.8% for P. intermedia, 63.4% for A. actinomycetemcomitans, 46.6% for T. forsythia, 46.6% for T. denticola, and 89.2% for F. nucleatum. Significant age- and BMI-related differences were observed in pathogen prevalence, particularly with P. gingivalis, P. intermedia, and T. denticola. Young obese individuals exhibited a higher prevalence of P. intermedia and T. forsythia. P. gingivalis was found to be associated with hypertension and dyslipidemia, while P. intermedia was linked to hypertension and obesity. T. denticola was associated with obesity, dyslipidemia and smoking, whereas T. forsythia was linked to dyslipidemia alone.ConclusionsThis study highlights the potential connection between periodontal pathogens and risk factors associated with cardiovascular disease, including smoking, elevated BMI, increased adipose tissue, hypertension, and dyslipidemia. Further research is required to determine the causal relationships between oral microbiome dysbiosis, obesity and, systemic diseases and to develop an effective strategy for preventing oral health-related CVD risk factors in young adults.